Cortical gyrification predicts initial treatment response in adults with ADHD - Laatsch, Jonathan; Stein, Frederike; Maier, Simon; Matthies, Swantje; Sobanski, Esther; Alm, Barbara; Tebartz van Elst, Ludger; Krug, Axel; Philipsen, Alexandra (Translational Psychiatry, 2025)
While the need for personalised treatment approaches grows in recognition, predicting treatment outcomes for adults with Attention-Deficit/Hyperactivity Disorder (ADHD) remains underexplored. Recent interest has turned to the brain’s surface and its association with treatment response. Although the precise interplay between cortical gyrification and ADHD treatment outcomes remains to be elucidated, preliminary investigations suggest a promising avenue for diagnostic innovation. Expanding upon the Comparison of Methylphenidate and Psychotherapy in Adult ADHD Study (COMPAS), we investigated the prognostic value of cortical gyrification in predicting treatment response. Specifically, we explored how pre-treatment cortical gyrification might predict response to psychotherapy or clinical management in combination with either methylphenidate or placebo following a 12-week intensive treatment period. Cortical gyrification was assessed using 121 T1-weighted anatomical scans. Linear regression models investigated the predictive value of cortical gyrification, regressing baseline cortical structure against post-treatment severity. All brain structural analyses were conducted using the threshold-free cluster enhancement (TFCE) approach and the Computational Anatomy Toolbox (CAT12) within the Statistical Parametric Mapping Software (Matlab Version R2021a). Results revealed significant positive region-specific associations between cortical gyrification and treatment response across three symptom dimensions, with significant associations localised predominantly in frontal regions of the left hemisphere. Our findings emphasise that increased cortical gyrification in frontal cortical regions signifies enhanced treatment efficacy following a 12-week intervention. Further research in this area is imperative to verify the reliability of biological markers in view of treatment success to potentially reduce unnecessary drug-related side-effects, minimising delay from receiving more effective treatments, and increase treatment adherence.